2012
DOI: 10.1016/j.molcel.2012.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Homology Recognition in DNA Recombination from Dual-Molecule Experiments

Abstract: In E. coli homologous recombination, a filament of RecA protein formed on DNA searches and pairs a homologous sequence within a second DNA molecule with remarkable speed and fidelity. Here, we directly probe the strength of the two-molecule interactions involved in homology search and recognition using dual-molecule manipulation, combining magnetic and optical tweezers. We find that the filament's secondary DNA-binding site interacts with a single strand of the incoming double-stranded DNA during homology samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 36 publications
4
89
0
Order By: Relevance
“…Further, we hypothesize that conformational proofreading is a common feature of damage recognition in the absence of energy consumption and is also used by XPC to discriminate damage. In this regard, it is interesting to note that conformational and kinetic proofreading mechanisms have been found to operate together for highly specific recognition of homologous sequences during homologous recombination (59,60). We believe that this synergy of damage detection mechanisms is required for the successful navigation of the complex kinetic and thermodynamic landscape of DNA damage recognition, which achieves high specificity by rejecting nonoptimal repair intermediates.…”
Section: Conformational Proofreading Is a Candidate Mechanism For Damagementioning
confidence: 99%
“…Further, we hypothesize that conformational proofreading is a common feature of damage recognition in the absence of energy consumption and is also used by XPC to discriminate damage. In this regard, it is interesting to note that conformational and kinetic proofreading mechanisms have been found to operate together for highly specific recognition of homologous sequences during homologous recombination (59,60). We believe that this synergy of damage detection mechanisms is required for the successful navigation of the complex kinetic and thermodynamic landscape of DNA damage recognition, which achieves high specificity by rejecting nonoptimal repair intermediates.…”
Section: Conformational Proofreading Is a Candidate Mechanism For Damagementioning
confidence: 99%
“…The correlation between directional zipping and stability provides an efficient target site search process, by only considering targets with sufficient homology directly at the start of the process and rejecting all others. Similar proofreading by directional zipping may be employed in other biological processes where homologous sequences need to be found, such as homologous recombination, where a wealth of off targets need to be discriminated (De Vlaminck et al, 2012). Crucial features of an efficient search process would be that the offtarget rejection is dependent on the length of the base-paired intermediate and that early mutations have a greater effect, as suggested by the wide-spread occurrence of seed sequences in other biological systems (Kü nne et al, 2014).…”
Section: Collapse Of Short R-loop Intermediates Ensures Efficient Tarmentioning
confidence: 99%
“…The importance of length-dependent sequence recognition as a means for rapidly rejecting incorrect sequences was first recognized by Charles Thomas, Jr. (60), who in 1966 suggested that it would be beneficial for recombination to take place between nonrepetitive minimal recognition lengths composed of "words" that can be uniquely identified within the genome, and these original concepts have been further elaborated by several groups (55,(61)(62)(63). Simply put, longer sequences are less common than shorter sequences, so there is a benefit to search for these longer sequences, which will also have a higher probability of being the correct homologous target (Fig.…”
Section: Theoretical Considerationsmentioning
confidence: 99%